Hemispherotomy Revised: A complication overview and a systematic review meta-analysis - Maria D. Karagianni; Alexandros G. Brotis; Anastasia Tasiou; Daniel Delev; Marec von Lehe; Olaf E.M.G. Schijns; Konstantinos N. Fountas (Brain and Spine, 2023)
Introduction: Hemispherectomy/hemispherotomy has been employed in the management of catastrophic epilepsy. However, initial reports on the associated mortality and morbidity raised several concerns regarding the technique's safety. Their actual, current incidence needs to be systematically examined to redefine hemispherotomy's exact role. Research question: Our current study examined their incidence and evaluated the association of the various hemispherotomy surgical techniques with the reported complications. Material & methods: A PRISMA-compliant systematic review and meta-analysis was performed. We searched PubMed, Scopus, and Web of Science until December 2022. Fixed- and random-effects models were employed. Egger's regression test was used for estimating the publication bias, while subgroup analysis was utilized for defining the role of the different hemispherotomy techniques. Results: We retrieved a total of 37 studies. The overall procedure mortality was 5%, with a reported mortality of 7% for hemispherectomy and 3% for hemispherotomy. The reported mortality has decreased over the last 30 years from 32% to 2%. Among the observed post-operative complications aseptic meningitis and/or fever occurred in 33%. Hydrocephalus requiring a shunt insertion occurred in 16%. Hematoma evacuation was necessary in 8%, while subgaleal effusion in another 8%. Infections occurred in 11%. A novel post-operative cranial nerve deficit occurred in 11%, while blood transfusion was necessary in 28% of the cases. Discussion and conclusion: Our current analysis demonstrated that the evolution from hemispherectomy to hemispherotomy along with neuroanesthesia advances, had a tremendous impact on the associated mortality and morbidity. Hemispherotomy constitutes a safe surgical procedure in the management of catastrophic epilepsies.